Surface-modified oxide solid electrolyte, method for preparing the same, and use thereof

CN122931069APending Publication Date: 2026-10-16ZHEJIANG ZHIBANG LITHIUM BATTERY NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611142360.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-05-19
Filing Date
2026-07-30
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0007]鉴于以上现有技术的不足之处,本发明提供了一种表面改性氧化物固态电解质的制备方法,以解决传统表面改性方法中界面层与氧化物固态电解质基体结合力弱、界面阻抗高、离子电导率偏低以及难以在室温下有效抑制锂枝晶生长等技术问题

Benefits of technology

本发明表面改性氧化物固态电解质的制备方法,通过创新性地在氧化物固态电解质表面依次进行离子液体单体接枝和乙二醇二乙烯基醚原位自由基共聚,形成化学键合的聚离子液体/聚醚复合包覆层。这一设计不仅实现了氧化物固态电解质表面的残碱转化与羟基失活,避免了界面副反应,而且通过离子液体单元的高离子电导率与乙二醇二乙烯基醚单元的柔性链段协同作用,构建了兼具快速锂离子传输和抑制锂枝晶生长的多功能界面层。这种设计不仅增强了固态电解质与锂金属负极的界面浸润性,将界面阻抗降低至传统未改性电解质的1/3以下,还保持了氧化物电解质本体优异的热稳定性和机械强度,有助于实现全固态锂金属电池在室温下的稳定循环。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The application discloses a preparation method of a surface-modified oxide solid electrolyte, which comprises the following steps: S1, reacting an oxide solid electrolyte matrix with a bifunctional ionic liquid modifying compound in the presence of a catalyst in an inert atmosphere to obtain an intermediate grafted with ionic liquid monomers on the surface; and S2, performing a free radical copolymerization reaction on the intermediate obtained in the step S1 and ethylene glycol divinyl ether monomers in the presence of an initiator to in-situ copolymerize the grafted ionic liquid monomers and the ethylene glycol divinyl ether monomers to form a polymer coating layer, thereby obtaining the surface-modified oxide solid electrolyte. The preparation method of the application not only eliminates the interface side reaction by chemically bonding the ionic liquid modifying compound and the residual alkali / hydroxyl on the surface of the electrolyte, but also in-situ synthesizes a poly ionic liquid / poly ether composite coating layer, which has the characteristics of high ionic conductivity and flexible chain segments, thereby significantly reducing the interface impedance and inhibiting the growth of lithium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of solid electrolytes, and more particularly to a surface-modified oxide solid electrolyte, its preparation method, and its application. Background Technology

[0002] Solid-state electrolytes are the core components of all-solid-state lithium batteries. Among them, oxide solid-state electrolytes (such as garnet-type LLZO, perovskite-type LLTO, and NASICON-type LATP) have attracted much attention due to their high room-temperature ionic conductivity, wide electrochemical window, and excellent thermal stability. However, oxide solid-state electrolytes still face the following bottlenecks in practical applications: (1) Poor interface contact: The oxide electrolyte and the electrode are in a rigid solid-solid contact with a large interface impedance, and the volume change of lithium metal during charging and discharging can easily lead to loss of contact.

[0003] (2) Interfacial side reactions: LLZO easily forms a residual Li2CO3 alkali layer in air, leading to lithium phobicity and increased interfacial resistance; Ti-containing oxides such as LATP react with lithium metal, causing Ti to react with lithium metal. 4+ The restoration caused the interface structure to collapse.

[0004] (3) Lithium dendrite growth: The ion flux at the interface is uneven, and lithium dendrites can easily penetrate the electrolyte along the grain boundary or pores, causing a short circuit.

[0005] To address the aforementioned issues, existing technologies have proposed various surface modification schemes. For example, surface treatment of oxide powders with organic acids (citric acid, oxalic acid, etc.) (CN121342507A) can introduce polar groups on the particle surface to improve dispersibility. However, the organic acids and electrolyte surfaces only have weak chemical bonds, making them prone to desorption during long-term cycling, and organic residues can reduce ionic conductivity. Another example is coating the surface of oxide ceramic sheets with a "salt-coated polymer" layer with high lithium salt content (CN114006033B). While this can reduce interfacial impedance, the polymer layer thickness reaches 10-50 μm, increasing the inactive volume resistivity, and good performance is only achieved at a high temperature of 60℃, limiting room temperature applications. Yet another example is using organic ether surfactants to hydrophobically modify LATP and LiTFSI to achieve aqueous film formation (CN120978230B). However, organic ethers are prone to migration and redistribution, and the long-term stability of LATP in water remains a problem. In addition, although grafting LATP surface residual alkali with benzothiophene derivative (CN118005648B) can partially suppress side reactions, the resulting surface layer is a rigid molecular layer, which cannot alleviate the stress caused by the volume expansion of lithium metal, and does not have a flexible buffering function.

[0006] Therefore, there is an urgent need to develop a surface modification method that can form stable chemical bonds with oxide electrolyte substrates, has high ionic conductivity, flexible buffering lithium dendrite growth capability, and can operate at room temperature. Summary of the Invention

[0007] In view of the shortcomings of the prior art, the present invention provides a method for preparing surface-modified oxide solid electrolytes to solve the technical problems of weak bonding between the interface layer and the oxide solid electrolyte matrix, high interface impedance, low ionic conductivity, and difficulty in effectively suppressing lithium dendrite growth at room temperature in traditional surface modification methods.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a surface-modified oxide solid electrolyte, the method comprising the following steps: S1: An intermediate of surface-grafted ionic liquid monomer is obtained by reacting an oxide solid electrolyte matrix with a bifunctional ionic liquid modified compound in the presence of a catalyst under an inert atmosphere. S2: The intermediate obtained in step S1 is subjected to a free radical copolymerization reaction with ethylene glycol divinyl ether monomer in the presence of an initiator, so that the grafted ionic liquid monomer and ethylene glycol divinyl ether monomer are copolymerized in situ to form a polymer coating layer, thereby obtaining the surface-modified oxide solid electrolyte.

[0009] As a preferred technical solution, the oxide solid electrolyte matrix is ​​selected from at least one of garnet-type LLZO, perovskite-type LLTO, and NASICON-type LATP.

[0010] As a preferred technical solution, the bifunctional ionic liquid modified compound has the structure shown in Formula I: Formula I; Where R1, R2, and R3 are all bromine; or at least one of R1, R2, and R3 is bromine, and the remainder is hydrogen, fluorine, or methyl; R4 is an olefinic group; R5 is methyl or ethyl; X - It contains fluoride anions.

[0011] The bifunctional ionic liquid modified compound of this invention, under the action of a catalyst, undergoes a nucleophilic substitution reaction between bromine atoms and metal hydroxyl groups (M-OH) on the surface of oxide solid electrolytes to generate MO-imidazolium cation covalent bonds. On the one hand, it transforms harmful residual alkalis such as Li2CO3 / LiOH on the electrolyte surface into a chemically bonded imidazolium cation layer, achieving in-situ transformation of residual alkalis and complete deactivation of hydroxyl active centers. This eliminates interfacial side reactions at the source and avoids Ti oxide-containing reactions such as LATP. 4+On the one hand, reduction issues are addressed; on the other hand, vinyl functional groups that can be polymerized by free radicals are introduced onto the electrolyte surface to provide covalent grafting anchors for the subsequent in-situ copolymerization of ethylene glycol divinyl ether monomers, ensuring the stability of the chemical bond between the coating layer and the electrolyte matrix.

[0012] As a preferred technical solution, the catalyst is at least one of triethylamine, potassium carbonate, and sodium carbonate; and / or the inert atmosphere is nitrogen, argon, or helium; and / or the reaction temperature is 40–120°C, and the reaction time is 2–24 h.

[0013] As a preferred technical solution, the ethylene glycol divinyl ether is at least one of ethylene glycol divinyl ether, diethylene glycol divinyl ether, and triethylene glycol divinyl ether.

[0014] As a preferred technical solution, the molar ratio of the ethylene glycol divinyl ether monomer to the ionic liquid monomer is 1:0.5 to 1:5.

[0015] As a preferred technical solution, the olefin group is one of vinyl, n-propenyl, or isopropenyl.

[0016] As a preferred technical solution, the fluorinated anion is at least one of hexafluorophosphate, tetrafluoroborate, or bis(trifluoromethanesulfonyl)imide.

[0017] Another aspect of the present invention is to provide a surface-modified oxide solid electrolyte, wherein the oxide solid electrolyte is prepared by the preparation method of the surface-modified oxide solid electrolyte described above.

[0018] Another aspect of the present invention is to provide the application of the surface-modified oxide solid electrolyte as described above in the preparation of all-solid-state lithium metal batteries.

[0019] The beneficial effects of this invention are: This invention discloses a method for preparing surface-modified oxide solid electrolytes. It innovatively involves sequentially grafting ionic liquid monomers onto the surface of the oxide solid electrolyte and then performing in-situ free radical copolymerization of ethylene glycol divinyl ether (EDE) to form a chemically bonded polyionic liquid / polyether composite coating layer. This design not only achieves residual alkali conversion and hydroxyl deactivation on the oxide solid electrolyte surface, avoiding interfacial side reactions, but also constructs a multifunctional interfacial layer that combines rapid lithium-ion transport and suppression of lithium dendrite growth through the synergistic effect of the high ionic conductivity of the ionic liquid units and the flexible segments of the EEDE units. This design not only enhances the interfacial wettability between the solid electrolyte and the lithium metal anode, reducing the interfacial impedance to less than one-third of that of traditional unmodified electrolytes, but also maintains the excellent thermal stability and mechanical strength of the oxide electrolyte bulk, contributing to the stable cycling of all-solid-state lithium metal batteries at room temperature.

[0020] More importantly, this invention employs an in-situ copolymerization strategy, where the coating layer is covalently grafted onto the electrolyte surface, avoiding interfacial delamination problems caused by physical mixing or simple coating, thus significantly improving long-term cycle stability. Simultaneously, the ether oxygen groups in the ethylene glycol divinyl ether monomer can form weak coordination with lithium ions, helping to increase ion transference number and suppress concentration polarization. Furthermore, fluorinated anions (such as TFSI) - The introduction of ) imparts hydrophobicity and a wide electrochemical window to the coating layer, making it suitable for high-voltage cathode systems.

[0021] In summary, the surface-modified oxide solid electrolyte of the present invention not only has excellent ionic conductivity and low interfacial impedance, but also can support all-solid-state lithium metal batteries to stably cycle at 1C rate for more than 500 cycles at room temperature with a capacity retention of more than 80%, which can meet the practical application requirements of next-generation high-energy-density and high-safety solid-state batteries. Detailed Implementation

[0022] The following description is intended to disclose the invention and enable those skilled in the art to implement it. The preferred embodiments described below are merely examples, and other obvious variations will occur to those skilled in the art.

[0023] Example 1 The preparation method of the surface-modified oxide solid electrolyte in this embodiment includes the following steps: S1: NASICON-type LATP (lithium aluminum titanium phosphate) powder with an impurity content of less than 0.1% and a particle size distribution D50 = 0.5 μm was selected as the oxide solid electrolyte matrix. 100 g of LATP powder was weighed and dispersed in 1000 mL of anhydrous tetrahydrofuran. 25 g of the bifunctional ionic liquid modifier compound and 1.5 g of sodium carbonate catalyst were added, and the mixture was stirred at 130 °C for 24 h under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times each with anhydrous ethanol and deionized water, and dried under vacuum at 60 °C for 12 h to obtain the intermediate of the surface-grafted ionic liquid monomer.

[0024] S2: 100g of the intermediate obtained in step S1 was dispersed in 800mL of anhydrous acetonitrile. Ethylene glycol divinyl ether monomer and azobisisobutyronitrile (AIBN) initiator were added, wherein the molar ratio of ethylene glycol divinyl ether monomer to the grafted ionic liquid monomer in step S1 was 1:2, and the amount of AIBN added was 1% of the total monomer mass. The reaction was carried out under nitrogen protection at 70℃ for 8h with stirring to conduct a free radical copolymerization reaction. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times each with anhydrous ethanol and deionized water, and dried under vacuum at 80℃ for 12h to obtain the surface-modified oxide solid electrolyte.

[0025] The preparation method of the bifunctional ionic liquid modified compound is as follows: 0.5 mol of 2,4,5-tribromo-1-vinylimidazolium and 0.6 mol of bromoethane are dissolved in an appropriate amount of acetonitrile. After nitrogen purging, the mixture is stirred at 80°C for 36 h. After the reaction is completed, the mixture is cooled to room temperature, and the reaction solution is slowly added dropwise to a large amount of ethyl acetate to precipitate. The solid is collected by filtration, washed three times with diethyl ether, and dried under vacuum to obtain a pale yellow solid product—1-vinyl-3-ethyl-2,4,5-tribromoimidazolium bromide. The solid product is dissolved in deionized water, and 1-vinyl-3-ethyl-2,4,5-tribromoimidazolium bromide and lithium bis(trifluoromethanesulfonyl)imide aqueous solution are added at a molar ratio of 1:1.1. The mixture is stirred at room temperature for 24 h for ion exchange reaction, and finally a bifunctional ionic liquid modified compound with bis(trifluoromethanesulfonyl)imide anion and containing vinyl and bromine elements is obtained. The chemical structure is as follows: .

[0026] Application Example 1 The surface-modified oxide solid electrolyte prepared in Example 1 was used to prepare an all-solid-state lithium metal battery. The specific steps are as follows: In an argon-atmospheric glove box (water and oxygen content <0.1ppm), 70mg of surface-modified oxide solid electrolyte powder was weighed and placed in a 12mm diameter stainless steel mold. It was then pressed under 300MPa pressure to obtain a solid electrolyte sheet with a thickness of approximately 300μm. Using lithium iron phosphate (LFP) as the positive electrode active material, it was mixed with the surface-modified oxide solid electrolyte prepared in Example 1, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) at a mass ratio of 70:20:5:5. An appropriate amount of N-methylpyrrolidone (NMP) was added and ground uniformly. The mixture was then coated onto the surface of aluminum foil, vacuum dried at 120℃ for 12h, and cut into 10mm diameter discs to obtain the positive electrode sheet. Using a lithium metal sheet as the negative electrode, the solid electrolyte sheet was placed between the positive and negative lithium electrode sheets to assemble a CR2032 type coin-type all-solid-state lithium metal battery.

[0027] Test results show that, at room temperature (25℃), the assembled all-solid-state lithium metal battery exhibits an initial discharge specific capacity of 158.6 mAh / g and a coulombic efficiency of 98.2% at 0.2C rate; after 100 cycles at 0.5C rate, the capacity retention is 92.7%; and after 500 cycles at 1C rate, the capacity retention is 86.3%. AC impedance testing shows an interface impedance of 42.5 Ω·cm. 2 Compared to the unmodified LATP-assembled battery (interfacial impedance of 187.3 Ω·cm), 2 The current density was reduced by approximately 77%. Critical current density testing showed that the battery achieved a current density of 1.2 mA / cm².2 It can still cycle stably at current densities without short circuits, demonstrating excellent ability to suppress lithium dendrite growth.

[0028] Example 2 The preparation method of the surface-modified oxide solid electrolyte in this embodiment includes the following steps: S1: Perovskite-type LLTO (lithium lanthanum titanium oxide) powder with an impurity content of less than 0.1% and a particle size distribution D50 = 0.5 μm was selected as the oxide solid electrolyte matrix. 100 g of LLTO powder was weighed and dispersed in 1000 mL of anhydrous tetrahydrofuran. 23 g of the bifunctional ionic liquid modifier compound and 1.5 g of potassium carbonate catalyst were added. The mixture was stirred and reacted at 120 °C for 24 h under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled to room temperature, filtered, and washed three times each with anhydrous ethanol and deionized water. It was then vacuum dried at 60 °C for 12 h to obtain the intermediate of the surface-grafted ionic liquid monomer.

[0029] S2: 100g of the intermediate obtained in step S1 was dispersed in 800mL of anhydrous acetonitrile. Diethylene glycol divinyl ether monomer and azobisisobutyronitrile (AIBN) initiator were added, wherein the molar ratio of diethylene glycol divinyl ether monomer to the grafted ionic liquid monomer in step S1 was 1:3, and the amount of AIBN added was 1% of the total monomer mass. The reaction was carried out under nitrogen protection at 70℃ for 8h with stirring to conduct a free radical copolymerization reaction. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times each with anhydrous ethanol and deionized water, and dried under vacuum at 80℃ for 12h to obtain the surface-modified oxide solid electrolyte.

[0030] The preparation method of the bifunctional ionic liquid modified compound is as follows: 0.5 mol of 2,4,5-tribromo-1-vinylimidazolium and 0.6 mol of bromomethane are dissolved in an appropriate amount of acetonitrile. After nitrogen purging, the mixture is stirred at 80 °C for 36 h. After the reaction is completed, the mixture is cooled to room temperature, and the reaction solution is slowly added dropwise to a large amount of ethyl acetate to precipitate. The solid is collected by filtration, washed three times with diethyl ether, and dried under vacuum to obtain a pale yellow solid product—1-vinyl-3-methyl-2,4,5-tribromoimidazolium bromide. The solid product is dissolved in deionized water, and a DMF organic solution of lithium hexafluorophosphate is added at a molar ratio of 1-vinyl-3-methyl-2,4,5-tribromoimidazolium bromide to lithium hexafluorophosphate of 1:1.1. The mixture is stirred at room temperature for 24 h for ion exchange reaction, and finally a bifunctional ionic liquid modified compound with bis(trifluoromethanesulfonyl)imide anion and containing vinyl and bromine elements is obtained.

[0031] Application Example 2 The surface-modified oxide solid electrolyte prepared in Example 2 was used to prepare an all-solid-state lithium metal battery. The specific steps are as follows: In an argon-atmosphere glove box (water and oxygen content <0.1ppm), 70mg of surface-modified oxide solid electrolyte powder was weighed and placed in a 12mm diameter stainless steel mold. It was then pressed under 300MPa pressure to obtain a solid electrolyte sheet with a thickness of approximately 300μm. Using lithium iron phosphate (LFP) as the positive electrode active material, it was mixed with the surface-modified oxide solid electrolyte prepared in Example 2, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) at a mass ratio of 70:20:5:5. An appropriate amount of N-methylpyrrolidone (NMP) was added and ground until uniform. The mixture was then coated onto the surface of aluminum foil, vacuum dried at 120℃ for 12h, and cut into 10mm diameter discs to obtain the positive electrode sheet. Using a lithium metal sheet as the negative electrode, the solid electrolyte sheet was placed between the positive and negative lithium electrode sheets to assemble a CR2032 type coin-type all-solid-state lithium metal battery.

[0032] Test results show that, at room temperature (25℃), the assembled all-solid-state lithium metal battery exhibits an initial discharge specific capacity of 156.3 mAh / g and a coulombic efficiency of 97.9% at 0.2C rate; after 100 cycles at 0.5C rate, the capacity retention is 91.5%; and after 500 cycles at 1C rate, the capacity retention is 85.1%. AC impedance testing shows an interface impedance of 48.2 Ω·cm. 2 Compared to unmodified LLTO-assembled batteries (interfacial impedance of 198.6 Ω·cm), 2 The current density was reduced by approximately 76%. Critical current density testing showed that the battery achieved a current density of 1.15 mA / cm². 2 It can still cycle stably at current densities without short circuits, demonstrating good ability to suppress lithium dendrite growth.

[0033] Example 3 The preparation method of the surface-modified oxide solid electrolyte in this embodiment includes the following steps: S1: Garnet-type LLZTO (lithium lanthanum zirconium tantalum oxide) powder with an impurity content of less than 0.1% and a particle size distribution D50 = 0.5 μm was selected as the oxide solid electrolyte matrix. 100 g of LLZTO powder was weighed and dispersed in 1000 mL of anhydrous tetrahydrofuran. 20 g of a bifunctional ionic liquid modified compound (same as in Example 1) and 1.5 g of catalyst (0.5 g of triethylamine and 1 g of sodium carbonate) were added. The mixture was stirred and reacted at 110 °C for 24 h under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times each with anhydrous ethanol and deionized water, and dried under vacuum at 60 °C for 12 h to obtain an intermediate of surface-grafted ionic liquid monomer.

[0034] S2: 100g of the intermediate obtained in step S1 was dispersed in 800mL of anhydrous acetonitrile. Triethylene glycol divinyl ether monomer and azobisisobutyronitrile (AIBN) initiator were added, wherein the molar ratio of triethylene glycol divinyl ether monomer to the grafted ionic liquid monomer in step S1 was 1:5, and the amount of AIBN added was 1% of the total monomer mass. The reaction was carried out under nitrogen protection at 70℃ for 8h with stirring to conduct a free radical copolymerization reaction. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times each with anhydrous ethanol and deionized water, and dried under vacuum at 80℃ for 12h to obtain the surface-modified oxide solid electrolyte.

[0035] Application Example 3 The surface-modified oxide solid electrolyte prepared in Example 3 was used to prepare an all-solid-state lithium metal battery. The specific steps are as follows: In an argon-atmospheric glove box (water and oxygen content <0.1ppm), 70mg of surface-modified oxide solid electrolyte powder was weighed and placed in a 12mm diameter stainless steel mold. It was then pressed under 300MPa pressure to obtain a solid electrolyte sheet with a thickness of approximately 300μm. Using lithium iron phosphate (LFP) as the positive electrode active material, it was mixed with the surface-modified oxide solid electrolyte prepared in Example 3, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) at a mass ratio of 70:20:5:5. An appropriate amount of N-methylpyrrolidone (NMP) was added and ground uniformly. The mixture was then coated onto the surface of aluminum foil, vacuum dried at 120℃ for 12h, and cut into 10mm diameter discs to obtain the positive electrode sheet. Using a lithium metal sheet as the negative electrode, the solid electrolyte sheet was placed between the positive and negative lithium electrode sheets to assemble a CR2032 type coin-type all-solid-state lithium metal battery.

[0036] Test results show that, at room temperature (25℃), the assembled all-solid-state lithium metal battery exhibits an initial discharge specific capacity of 160.2 mAh / g and a coulombic efficiency of 98.5% at 0.2C rate; after 100 cycles at 0.5C rate, the capacity retention is 93.8%; and after 500 cycles at 1C rate, the capacity retention is 87.9%. AC impedance testing shows an interface impedance of 39.8 Ω·cm. 2 Compared to batteries assembled with unmodified LLZTO (interfacial impedance of 165.4 Ω·cm), 2 The current density was reduced by approximately 76%. Critical current density testing showed that the battery achieved a current density of 1.35 mA / cm². 2 It can still cycle stably at current densities without short circuits, demonstrating excellent ability to suppress lithium dendrite growth.

[0037] Comparative Example 1 The preparation method of the surface-modified oxide solid electrolyte in this comparative example is basically the same as that in Example 1 in terms of raw material composition and preparation steps. The difference is that step S2 (i.e., the free radical copolymerization reaction with ethylene glycol divinyl ether monomer) is omitted in the preparation method of this comparative example.

[0038] The surface-modified oxide solid electrolyte prepared in Comparative Example 1 was used to prepare an all-solid-state lithium metal battery, and the specific steps were the same as in Application Example 1.

[0039] Test results show that, at room temperature (25℃), the assembled all-solid-state lithium metal battery exhibits an initial discharge specific capacity of 142.3 mAh / g and a coulombic efficiency of 95.1% at 0.2C rate. After 100 cycles at 0.5C rate, the capacity retention is 78.6%. After 300 cycles at 1C rate, the capacity retention is 62.4% (decreasing to 48.7% after 500 cycles). AC impedance testing shows an interface impedance of 98.6 Ω·cm. 2 Compared to Example 1 (42.5 Ω·cm) 2 The critical current density (CCD) increased significantly. Critical current density testing showed that the battery reached 0.65 mA / cm². 2 A short circuit occurs at the specified current density, and the ability to suppress lithium dendrite growth is significantly weaker than in Example 1. This indicates that after omitting the in-situ copolymerization of polyether in step S2, the ionic liquid graft layer alone cannot provide sufficient flexible buffering and uniform lithium-ion flux regulation capability, resulting in a significant decrease in interface stability and cycle performance.

[0040] Comparative Example 2 The preparation method of the surface-modified oxide solid electrolyte in this comparative example is basically the same as that in Example 1 in terms of raw material composition and preparation steps. The difference is that in the preparation method of this comparative example, step S1 (i.e., the surface grafting of ionic liquid monomers is not performed) is omitted, and the oxide solid electrolyte matrix is ​​directly copolymerized with ethylene glycol divinyl ether monomer by free radical copolymerization.

[0041] The surface-modified oxide solid electrolyte prepared in Comparative Example 2 was used to prepare an all-solid-state lithium metal battery, and the specific steps were the same as in Application Example 1.

[0042] Test results show that, at room temperature (25℃), the assembled all-solid-state lithium metal battery has an initial discharge specific capacity of 135.8 mAh / g and a coulombic efficiency of 94.3% at 0.2C rate; after 100 cycles at 0.5C rate, the capacity retention is 72.5%; after 300 cycles at 1C rate, the capacity retention is 55.6% (after 500 cycles, the capacity retention drops to 41.3%). AC impedance testing shows an interface impedance of 118.4 Ω·cm. 2The efficiency was significantly higher than that of Example 1 and unmodified LATP. Scanning electron microscopy revealed significant delamination of the polyether layer from the electrolyte surface after cycling. Critical current density testing showed that the battery achieved a critical current density of 0.55 mA / cm². 2 A short circuit occurs at the specified current density. This indicates that, omitting the chemical grafting step S1, the polyether layer only adheres to the electrolyte surface through physical coating, lacking covalent anchoring. It is prone to peeling off during cycling and cannot eliminate interfacial side reactions (residual alkali on the LATP surface and Ti). 4+ (The reduction problem has not been solved), resulting in high interface impedance and poor cycle stability.

[0043] Comparative Example 3 The preparation method of the surface-modified oxide solid electrolyte in this comparative example is basically the same as that in Example 1 in terms of raw material composition and preparation steps. The difference is that in the preparation method of this comparative example, ethylene glycol divinyl ether monomer is not added in step S2, and the grafted ionic liquid monomer is allowed to undergo self-homogenization in the presence of an initiator (azobisisobutyronitrile).

[0044] The surface-modified oxide solid electrolyte prepared in Comparative Example 3 was used to prepare an all-solid-state lithium metal battery, and the specific steps were the same as in Application Example 1.

[0045] Test results show that, at room temperature (25℃), the assembled all-solid-state lithium metal battery has an initial discharge specific capacity of 148.6 mAh / g and a coulombic efficiency of 96.8% at 0.2C rate; after 100 cycles at 0.5C rate, the capacity retention is 83.5%; and after 500 cycles at 1C rate, the capacity retention is 71.2%. AC impedance testing shows an interface impedance of 76.3 Ω·cm. 2 Although superior to unmodified LATP (187.3 Ω·cm) 2 However, it was significantly higher than that of Example 1 (42.5 Ω·cm). 2 Critical current density tests show that this battery achieves a current density of 0.85 mA / cm². 2 A short circuit occurs at a current density of [value missing], and its ability to suppress lithium dendrite growth is weaker than in Example 1 (1.20 mA / cm²). 2 Scanning electron microscopy revealed that the homopolymerized polyionic liquid layer was relatively rigid and lacked the buffering capacity of flexible segments, resulting in microcracks after cycling.

[0046] This indicates that although the ionic liquid homopolymer coating layer (Comparative Example 3) can eliminate some interfacial side reactions through chemical grafting, the coating layer lacks flexibility due to the absence of flexible polyether segments provided by ethylene glycol divinyl ether. It cannot effectively buffer the stress caused by the volume expansion of lithium metal. At the same time, the weak coordination between the ether oxygen group in the polyether segment and lithium ions is missing, resulting in lower ionic conductivity and interfacial stability than in Example 1.

[0047] Comparative Example 4 The preparation method of the surface-modified oxide solid electrolyte in this comparative example is basically the same as that in Example 1 in terms of raw material composition and preparation steps. The difference is that the surface grafting step S1 is not performed in the preparation method of this comparative example. Instead, the ionic liquid monomer and the ethylene glycol divinyl ether monomer are prepolymerized into a polymer and then physically mixed with the oxide electrolyte (i.e., non-in-situ composite). The specific steps are as follows: S1 (omitted): The LATP powder is not subjected to ionic liquid monomer grafting treatment. The original LATP powder (same as in Example 1, impurity content less than 0.1%, particle size distribution D50=0.5μm) is used directly as raw material.

[0048] S2 (modified as prepolymer followed by physical mixing): Pre-preparation of PIL-PEGDE copolymer: The bifunctional ionic liquid modified compound (same as in Example 1, 0.045 mol) and ethylene glycol divinyl ether monomer (molar ratio of ethylene glycol divinyl ether to ionic liquid monomer is 1:2, 0.0225 mol) were dissolved in 200 mL of anhydrous acetonitrile. Azobisisobutyronitrile (1% of the total monomer mass) was added as an initiator. The mixture was stirred at 70 °C for 8 h under nitrogen protection to carry out a free radical copolymerization reaction. After the reaction was completed, the mixture was cooled to room temperature, and the solvent was removed by vacuum distillation to obtain the PIL-PEGDE copolymer solid.

[0049] 100g of the original LATP powder was physically ground and mixed with the above-mentioned PIL-PEGDE copolymer in a mortar for 30min, then dispersed in 800mL of anhydrous acetonitrile and stirred for 2h. After filtration, the mixture was washed three times each with anhydrous ethanol and deionized water, and then vacuum dried at 80℃ for 12h to obtain the surface-modified oxide solid electrolyte.

[0050] The surface-modified oxide solid electrolyte prepared in Comparative Example 4 was used to prepare an all-solid-state lithium metal battery, and the specific steps were the same as in Application Example 1.

[0051] Test results show that, at room temperature (25℃), the assembled all-solid-state lithium metal battery exhibits an initial discharge specific capacity of 131.5 mAh / g and a coulombic efficiency of 93.6% at 0.2C rate. After 100 cycles at 0.5C rate, the capacity retention is 68.3%. After 300 cycles at 1C rate, the capacity retention is 51.8% (decreasing to 38.5% after 500 cycles). AC impedance testing shows an interface impedance of 135.7 Ω·cm. 2 It is only slightly better than unmodified LATP (187.3 Ω·cm). 2Scanning electron microscopy revealed significant phase separation between the PIL-PEGDE copolymer and LATP particles after cycling, with the copolymer detaching from the electrolyte surface. Critical current density testing showed that the battery achieved a critical current density of 0.48 mA / cm². 2 A short circuit occurs at a current density of [insert value here]. XPS analysis shows that residual alkali and Ti on the LATP surface [indicate this]. 4+ The reduction problem has not been effectively suppressed.

[0052] This indicates that, using a pre-copolymerization followed by physical mixing method (Comparative Example 4), the PIL-PEGDE copolymer only adheres to the LATP surface through physical adsorption, lacking covalent bond anchoring, and is prone to peeling and phase separation during cycling; simultaneously, due to the absence of the S1 chemical grafting step, the residual alkali on the LATP surface is not converted, and Ti... 4+ The reduction side reactions when in contact with lithium metal cannot be effectively suppressed, resulting in high interfacial impedance and poor cycle stability.

[0053] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. A method for preparing a surface-modified oxide solid electrolyte, characterized in that, The preparation method includes the following steps: S1: An intermediate of surface-grafted ionic liquid monomer is obtained by reacting an oxide solid electrolyte matrix with a bifunctional ionic liquid modified compound in the presence of a catalyst under an inert atmosphere. S2: The intermediate obtained in step S1 is subjected to a free radical copolymerization reaction with ethylene glycol divinyl ether monomer in the presence of an initiator, so that the grafted ionic liquid monomer and ethylene glycol divinyl ether monomer are copolymerized in situ to form a polymer coating layer, thereby obtaining the surface-modified oxide solid electrolyte.

2. The method for preparing the surface-modified oxide solid electrolyte as described in claim 1, characterized in that, The oxide solid electrolyte matrix is ​​selected from at least one of garnet-type LLZO, perovskite-type LLTO, and NASICON-type LATP.

3. The method for preparing the surface-modified oxide solid electrolyte as described in claim 1, characterized in that, The bifunctional ionic liquid modified compound has the structure shown in Formula I: Equation I; Where R1, R2, and R3 are all bromine; or at least one of R1, R2, and R3 is bromine, and the remainder is hydrogen, fluorine, or methyl; R4 is an olefinic group; R5 is methyl or ethyl; X - It contains fluoride anions.

4. The method for preparing the surface-modified oxide solid electrolyte as described in claim 1, characterized in that, The catalyst is at least one of triethylamine, potassium carbonate, and sodium carbonate; and / or the inert atmosphere is nitrogen, argon, or helium; and / or the reaction temperature is 40–120°C, and the reaction time is 2–24 h.

5. The method for preparing the surface-modified oxide solid electrolyte as described in claim 1, characterized in that, The ethylene glycol divinyl ether is at least one of ethylene glycol divinyl ether, diethylene glycol divinyl ether, and triethylene glycol divinyl ether.

6. The method for preparing the surface-modified oxide solid electrolyte as described in claim 1, characterized in that, The molar ratio of the ethylene glycol divinyl ether monomer to the ionic liquid monomer is 1:0.5 to 1:

5.

7. The method for preparing the surface-modified oxide solid electrolyte as described in claim 3, characterized in that, The olefin group is one of vinyl, n-propenyl, or isopropenyl.

8. The method for preparing the surface-modified oxide solid electrolyte as described in claim 3, characterized in that, The fluorinated anion is at least one of hexafluorophosphate, tetrafluoroborate, or bis(trifluoromethanesulfonyl)imide.

9. A surface-modified oxide solid electrolyte, characterized in that, The oxide solid electrolyte is prepared using the preparation method of the surface-modified oxide solid electrolyte as described in any one of claims 1 to 8.

10. The application of the surface-modified oxide solid electrolyte as described in claim 9 in the preparation of all-solid-state lithium metal batteries.

Citation Information

Patent Citations

  • Salt-coated polymer interfacial protective layer on solid electrolyte surface and its preparation method

    CN114006033B

  • A solid electrolyte and preparation method thereof, positive electrode material and lithium ion battery

    CN118005648B

  • A water-based composite electrolyte membrane and solid-state battery

    CN120978230B

  • Preparation method of low-cost and easy-to-process oxide solid electrolyte

    CN121342507A